THE EFFECTIVENESS OF THE FAMILY PLANNING PROGRAM IN CONTROLLING THE POPULATION GROWTH RATE IN NORTH MINAHASA REGENCY, NORTH SULAWESI PROVINCE - Rully Sumual; Arnold Poli; Hestiwati Basir; Djonny Pabisa (Registratie, 2024)
This research aims to assess the effectiveness of the Family Planning Program in controlling the population growth rate in North Minahasa Regency, North Sulawesi Province. The research employs a qualitative descriptive method to collect and analyze data, with a total of 9 informants. Data collection was conducted through observation, interviews, and documentation. The data analysis process involved reduction, presentation, conclusion, and verification. The research is grounded in Duncan's theory of effectiveness, which consists of three components: (1) Goal Achievement, (2) Integration, and (3) Adaptation. The findings indicate that the Family Planning Program has effectively reduced the population growth rate in North Minahasa Regency by 0.6% compared to the previous year. The success of the program can be attributed to efforts to address various challenges, including enhancing human resource competency through training, conducting continuous socialization during key family-related events, and improving infrastructure, such as providing transportation to facilitate access to services for family planning participants. Keywords: Effectiveness, Family Planning Program, Population Growth Rate